nab-Paclitaxel: Novel Clinical and Experimental Evidence in Pancreatic Cancer - Neesse, A.; Michl, P.; Tuveson, D. A.; Ellenrieder, V. (Zeitschrift für Gastroenterologie, 2014)
The past few decades have seen virtually no treatment advances for patients with metastatic pancreatic cancer. Clinical hallmark features of pancreatic ductal adenocarcinoma (PDA) include late symptom onset, invasive growth, early liver and lymph node metastasis, and resistance to available chemotherapies. nab-Paclitaxel (Abraxane®) is generated through high-pressure homogenization of human albumin and conventional paclitaxel resulting in non-covalently bound, water-soluble albumin-paclitaxel particles with an approximate diameter of 130 nm. Results from the recently completed Metastatic Pancreatic Adenocarcinoma Trial (MPACT) (phase III trial) showed a significant survival benefit for patients treated with nab-paclitaxel in combination with gemcitabine, and this treatment regimen is currently being implemented in national and international guidelines for PDA patients. Therefore, this regimen provides a much needed vantage point of attack for this recalcitrant tumor offering potential new hope for our patients. Mechanisms such as stromal depletion, selective intratumoral accumulation, synergism with gemcitabine metabolism and secreted protein acidic and rich in cysteine (SPARC) mediated anti-tumor activity have been suggested for nab-paclitaxel. This review discusses the clinical and experimental advances of nab-paclitaxel in pancreatic cancer.
Keywords: Pankreaskarzinom; Therapieresistenz; Medikamentenanflutung; nab-Paclitaxel